ISLAMIC POLITICAL THOUGHT AS IBADAH: Reinterpreting Hassan Hanafi’s Progressive Vision - Huda, Khoirul; Yudha, Dian Pratama; Ibbna, Mulazi (Islamijah: Journal of Islamic Social Sciences, 2025)
Research on Hassan Hanafi's political thought focuses on three main aspects. First, the concept of "Leftist Islam," which emphasizes the struggle against social injustice toward the poor and the oppressed, while promoting the principle of equal rights and responsibilities for all citizens. Second, Occidentalism, which refers to a critical study of Western civilization from a comprehensive social perspective, including an analysis of its strengths and weaknesses. Third, the hermeneutical approach, which is a method of interpreting the Qur’an in a modern context. Hassan Hanafi's thought has received mixed responses from Muslim intellectuals some support his ideas, while many others offer critiques. Among the scholars who have examined his ideas are Fazlur Rahman, Mohammed Arkoun, and Nurcholish Madjid, while Kuntowijoyo is among his critics. Despite differing opinions, these do not necessarily diminish the value of Hassan Hanafi’s thought. Some of his ideas remain relevant as sources of inspiration for efforts to rebuild Islamic civilization. This relevance can also be evaluated from the perspective of the Qur’an.